2012
DOI: 10.1002/bltj.20531
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Video Quality Assessment of HTTP Adaptive Streaming Technologies

Abstract: HTTP adaptive steaming (HAS) is becoming ubiquitous as a reliable method of delivering video content over the open Internet to a variety of devices fromBy introducing various network impairments, we were able to demonstrate that video quality gracefully declined until network conditions became too harsh. As a baseline, we compared them with the Microsoft Mediaroom* Internet Protocol television (IPTV) solution currently deployed by service providers. The HD content was encoded at 6.0 Mb/s.The second approach wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 10 publications
1
53
0
Order By: Relevance
“…Robinson et al [30] conducted a subjective study to evaluate user experience on HAS based video streaming under constrains of varying bandwith, latency, and video-data losses. Various observations were made including the preference of constant bitrate over frequently changing bitrate and a slow drop to the lower quality over oscillating bitrates.…”
Section: Related Workmentioning
confidence: 99%
“…Robinson et al [30] conducted a subjective study to evaluate user experience on HAS based video streaming under constrains of varying bandwith, latency, and video-data losses. Various observations were made including the preference of constant bitrate over frequently changing bitrate and a slow drop to the lower quality over oscillating bitrates.…”
Section: Related Workmentioning
confidence: 99%
“…Switching frequency also impacts QoE, as highly frequent quality variations may be annoying to the user [8][9][10][11][12][13]. Additionally, there is an interaction between frequency and amplitude of switches.…”
Section: What We Do Knowmentioning
confidence: 99%
“…Many studies have addressed the "to switch or not to switch" dilemma [8][9][10][11][12][13][14][15][16], with the result that constant quality is usually preferred to varying quality. In particular: short-term spikes may severely degrade the perceived quality [12]; constant (even lower) quality is preferred to decreasing quality (from higher to lower) [10]; constant or nearly constant quality is preferable to frequently varying quality, even if mean quality is lower [9,13]. In general, providing a bitrate as high as possible does not necessarily lead to the highest QoE [11].…”
Section: What We Do Knowmentioning
confidence: 99%
“…Studied presented in [3,8] revealed that the effect of spatial and temporal switching varies depending on the content type. This was found to be even true for switches with the same amplitude so that it is difficult to spot quality oscillation when there are frequent scene changes while in steady shots they are more noticeable.…”
Section: Introductionmentioning
confidence: 99%
“…The idea behind designing this method was to simulate realistic viewing conditions by using longer sequences so the observers become more engaged to the content as they would be in real life, rather than focusing on detecting impairments, which can happen using traditional methodologies with the short and less entertaining test videos. In this sense, another study was presented in [8], where the effect of different switching strategies were investigated, such that each individual adaptation event was evaluated in a sequence of around 2 min.…”
Section: Introductionmentioning
confidence: 99%